Unconventional Route to Uniform Hollow Semiconducting Nanoparticles with Tailorable Dimensions, Compositions, Surface Chemistry, and Near‐Infrared Absorption. (10th August 2017) - He, Yanjie; Pang, Xinchang; Jiang, Beibei; Feng, Chaowei; Harn, Yeu‐Wei; Chen, Yihuang; Yoon, Young Jun; Pan, Shuang; Lu, Cheng‐Hsin; Chang, Yajing; Zebarjadi, Mona; Kang, Zhitao; et al.
Abstract: Despite impressive recent advances in the synthesis of lead chalcogenide solid nanoparticles, there are no examples of lead chalcogenide hollow nanoparticles (HNPs) with controlled diameter and shell thickness as current synthetic approaches for HNPs have inherent limitations associated with their complexity, inability to precisely control the dimensions, and limited possibilities with regard to applicable materials. Herein, we report on an unconventional strategy for crafting uniform lead chalcogenide (PbS and PbTe) HNPs with tailorable size, surface chemistry, and near‐IR absorption. Amphiphilic star‐like triblock copolymers [polystyrene‐block‐poly(acrylic acid)‐block‐polystyrene and polystyrene‐block‐poly(acrylic acid)‐block‐poly(3, 4‐ethylenedioxythiophene)] were rationally synthesized and exploited as nanoreactors for the formation of uniform PbS and PbTe HNPs. Compared to their solid counterparts, the near‐IR absorption of the HNPs is blue‐shifted owing to the hollow interior. This strategy can be readily extended to other types of intriguing low‐band‐gap HNPs for diverse applications.